Genomic characterization, antimicrobial resistance, and virulence profiling of Escherichia coli isolated from diarrheic calves in Gansu, China - Meng, Qi; Chang, Liang; Wang, Shengming; Lu, Guopeng (Frontiers in Microbiology, 2026)
IntroductionThis study provides a comprehensive genomic investigation of Escherichia coli isolated from diarrheic calves in Gansu Province, China, a region with significant livestock production.MethodsWe employed whole-genome sequencing on 15 isolates from 15 different farms to characterize their molecular subtypes, plasmid repertoires, virulence gene profiles, and antibiotic resistance mechanisms.ResultsOur analysis revealed high genetic diversity with 10 sequence types and 9 serotypes, including a novel serogroup. Phenotypic testing demonstrated widespread multidrug resistance, yet canonical resistance genes were absent in many resistant strains. Phylogenetic analysis elucidated the roles of both clonal dissemination and horizontal gene transfer.DiscussionThese findings highlight the extensive genomic complexity of bovine E. coli in this region. The discrepancy between observed resistance and its genotypic basis underscores the need for integrated molecular surveillance. The small sample size limits generalizability, warranting confirmation in larger studies. This work situates its importance within the global “One Health” framework.